2002
DOI: 10.1080/10611860290022651
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Formulation for Superparamagnetic Iron Oxide (SPIO) Particles Enhancing MR Lymphography: Comparison of Physicochemical Properties and The In Vivo Behaviour

Abstract: The major aim of this study was to prove or disprove the theories concerning the correlation between physicochemical properties of superparamagnetic iron oxide (SPIO) particles and their accumulation in the lymph nodes. New SPIO particles were produced using starch as stabilising polymer shell. The synthesis was done in a two-step procedure using conventional wet-chemical precipitation technique and subsequent coating of the iron oxide cores. The particles were physicochemically characterised and their lymphot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 31 publications
(39 reference statements)
1
41
0
1
Order By: Relevance
“…82,86,95,155 Specifically, the SPIO extravasate from the vasculature to the interstitial space where they are transported to the lymph nodes via the lymphatic vessels. The absence of SPIO in lymph nodes as determined by MR imaging has been shown to correlate with disturbances in lymph node flow or architecture due to the presence of metastases.…”
Section: Lymph Node Imagingmentioning
confidence: 99%
“…82,86,95,155 Specifically, the SPIO extravasate from the vasculature to the interstitial space where they are transported to the lymph nodes via the lymphatic vessels. The absence of SPIO in lymph nodes as determined by MR imaging has been shown to correlate with disturbances in lymph node flow or architecture due to the presence of metastases.…”
Section: Lymph Node Imagingmentioning
confidence: 99%
“…In this way, USPIONs are used as contrast for lymphography 44,45 and angiography, 46,47 as a bone marrow contrast, or as a perfusion agent in brain and kidney.…”
mentioning
confidence: 99%
“…In another study, Mao et al evaluated the effect of polycaprolactone coating on the cytotoxicity of gold nanoparticles, and they found that polycaprolactonecoated gold nanoparticles had much less cytotoxicity than bare gold nanoparticles (Mao et al, 2007). It was also pointed out that surface coatings reduce the aggregation and toxicity of magnetic nanoparticles (Lind et al, 2002;Zavisova et al, 2015).…”
Section: Introductionmentioning
confidence: 99%